Syibhul Iddah as a Form of Justice for Women Mubadalah Perspective - Resa, Teresa; Kurniawan, Cecep Soleh (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2023)
Iddah is one of the consequences that women must undergo after a divorce, whether in divorce due to divorce, or divorce due to death. The Quranic provision on iddah is an absolute provision that must be followed. The legal basis for iddah is found in the Qur'an letter Al-Baqarah verse 228, letter Al-Ahzab verse 49. Iddah obligations are also regulated in the Compilation of Islamic Law (KHI) in article 170 paragraph 1 the wife is obliged to observe the iddah period, while in article 170 paragraph 2 it is explained that men observe the iddah period according to propriety. Of course, this has experienced problems in terms of relations between husband, wife and children, the families concerned, and women again experience discrimination where women have to run the iddah period according to a predetermined time while men do not run this appropriate term there is no specification of the length of time that is run, it seems that it is only a formality. The purpose of this research is to find out whether syibul iddah is a form of justice for women, to find out the impact of benefits for women and men with the existence of syibhul iddah in the view of maslahah mursalah and syibhul iddah as legal reform (social engineering) in Indonesia. This paper uses a library research method, using a descriptive analysis approach, namely by describing the text in KHI and other regulations in Indonesia regarding the existence of iddah then analysed using mubadalah. From this explanation, the result of the author's analysis is that syibhul iddah has a good impact on household relations because it provides justice for women and also provides benefits for the prevention of covert polygamy against women. Syibhul Iddah is needed in life as a legal reform (social engineering).Keywords: Syibhul Iddah, Mubadalah, Maslahah Mursalah, Social Engineering.